Applicazione della meccanica della frattura viscoelastica alla previsione della vita di tubi in polibutene - Luca Andena; Marta Rink; Roberto Frassine (Fracture and Structural Integrity)
Isotactic polybutene-1 (i-PB1) is a polymer used for the manufacturing of pressurized pipes. In this work two grades of i-PB1 with a different degree of isotacticity have been investigated; they have been supplied by Basell Polyolefins. Fracture tests have been performed at various temperatures and testing speeds. Two configurations have been used, single edge notch bending (SENB) and double cantilever beam (DCB), the latter only to study crack propagation. Optical methods have been used to detect crack initiation and measure propagation speed. From the phenomenological point of view, the formation of highly stretched material regions has been observed during crack propagation. A continuous tearing of these regions as the crack advances has often been interrupted by their sudden rupture, with the load decreasing accordingly. This partial instability has been observed on both material grades, with both testing configurations. Results of the tests have been interpreted using the fracture mechanics framework; a time-temperature superposition scheme has been adopted to represent viscoelastic behavior over several decades. An analytical model has been applied to predict the lifetime of pressurized pipes. A good agreement has been reported between model predictions and experimental data obtained from tests on polybutene pipes.